Antagonistic Activity and Surface Decontaminant Potential of Lactic Acid Bacteria from Fermented Oreochromis niloticus - Hazlina Ahamad Zakeri; Mohd Nizam Lani; Adilah Ismail; Nur Najihah Hasim; Rozila Alias; Azlina Mansor; Zaiton Hassan (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Lactic acid bacteria (LAB) have been extensively explored as potential biopreservants. They could produce substances with antimicrobial properties such as bacteriocins and organic acids which can also be the cause of antagonistic activity shown by LAB. Thus, the objective of this study is to assess the antagonistic activity of LAB isolated from fermented Oreochromis niloticus against foodborne pathogens and to determine the potential of LAB as a surface decontaminant of raw chicken breast and Tilapia fish fillet. The antagonistic activity of LAB has been shown to affect Escherichia coli, Salmonella typhimurium, and Staphylococcus aureus. When LAB was introduced to the mixed cultures of E. coli, S. typhimurium, and S. aureus, the growth of those pathogens drastically reduced and this has proven that LAB grows stronger and more stable while eliminating the pathogens. LAB and their cell-free supernatant (CFS) were also introduced into the raw chicken breast and fresh Tilapia fish fillet, where E. coli growth was recorded. Both cell cultures and CFS of LAB showed inhibition of E. coli on chicken breast and Tilapia fish fillet in the range of 0.16 to 1.28 log10 reduction and 0.12 to 1.12 log10 reduction, respectively. In conclusion, the results above suggest that LAB isolated from fermented O. niloticus has the potential to be a surface decontaminant. Additionally, both LAB and their CFS can also be used as biopreservative for both chicken breast and fish fillet due to a very good antagonistic activity shown by the LAB toward the foodborne pathogens.